Hafit period fuelwood preferences associated with early copper production at Building V, al-Khashbah, Oman - Proctor, Lucas; Döpper, Stephanie; Schmidt, Conrad (Proceedings of the Seminar for Arabian Studies, 2024)
Analyses of archaeological fuel remains can provide insight into pyrotechnologies, resource management, and the local environment. In this paper, we examine archaeological charcoals from Hafit period (3300–2700 BC) levels in Building V at al‑Khashbah (al-Khashaba), Oman, to understand fuel harvesting and burning preferences associated with early copper production. Building V is currently thought to be the earliest identified copper-production site in Oman based on the presence of abundant pyrotechnological remains, copper slag, and stratified radiocarbon results. Here, we build on previous anthracological work reconstructing woodland composition from the site. Anthracologists are increasingly recognising that fuelwood collection is often based on social or functional grounds rather than species availability. To that end, we have combined traditional taxonomic analysis with the application of dendro-anthracological methods to examine how intensive wood harvesting was for copper production and whether it had effects on the local vegetation. Dendrological reconstruction of wood calibre and condition at burning combined with spatial patterning of remains provides a more nuanced view of these preferences than can be achieved through taxonomic analysis alone.